Analysis of Economic Growth in ASEAN Countries - Anggraini, Dina Eka; Riyanto, Wahyu Hidayat; Suliswanto, Muhammad Sri Wahyudi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2020)
This studied aims to explained the effect of the variables of inflation, consumption expenditure, capital formation, foreign direct investment, and trade openness on gross domestic product ASEAN countries from 1996 – 2018. This research used a panel regression analyzed method to test the data in getting decisions. The t-statistic test results showed that consumption expenditure, capital formation, foreign direct investment, and trade openness significantly influence the direction of a positive relationship to gross domestic product. However, inflation showed a negative direction and had a significant effect on the gross domestic product so that if there is increased inflation it will reduce gross domestic product. The government can formula a single-digit policy so that there is no decline in the gross domestic product of ASEAN countries.